PENCIPTAAN BATIK POSTMODERN (Pengadaptasian Elemen Artistik Lukisan Modern Indonesia dalam Teknik dan Motif Batik Tradisional Yogyakarta) - Aruman Aruman; Deni Junaedi; Isbandono Hariyanto (Institut Seni Indonesia Yogyakarta, 2014)
Over time, traditional batik art continue to be explored and developed by a community ofsupporters. Various techniques and styles continue to emerge and inspire each other. Recognized theexistence of the world community. Likewise with modern Indonesian painting, to date the work andthe artist is able to leave a deep imprint for generations thereafter until today.Starting from the traditional batik and painting modern Indonesia, known to this day -through the creation of research - development possibilities of adapting the technique of batik andmodern painting techniques, so as to give birth to a new style that can contribute to the survival ofYogyakarta batik. From the analysis of the traditional batik of Yogyakarta and painting modernIndonesia, found a wide variety of painting techniques and artistic elements that can be combinedand used in batik techniques, in this case a blend of traditional and artistic batik art modern paintingbatik can be categorized as postmodernism, lifting the spirit of the old with a new style.Keywords: motif, batik, postmodernism, painting, Yogyakarta Seiring berjalannya waktu, seni batik tradisional terus digali dan dikembangkan olehmasyarakat pendukungnya. Berbagai teknik dan gaya terus bermunculan dan saling menginspirasi.Eksistensinya diakui masyarakat dunia. Begitu juga dengan seni lukis modern Indonesia, hingga saatini karya dan senimannya mampu meninggalkan jejak yang mendalam bagi generasi setelahnyahingga saat ini.Berawal dari batik tradisional dan lukisan modern Indonesia yang dikenal hingga saat ini -melalui penelitian penciptaan - dikembangkan kemungkinan-kemungkinan pengadaptasian teknikbatik dan teknik lukis modern, sehingga mampu melahirkan gaya baru yang dapat disumbangkanbagi kelangsungan batik di Yogyakarta. Dari hasil analisa batik tradisional Yogyakarta dan seni lukismodern Indonesia, didapati berbagai macam teknik lukis dan elemen artistik yang dapat dipadukandan digunakan dalam teknik membatik, dalam hal ini perpaduan seni batik tradisional dan artistikseni lukis modern dapat dikategorikan sebagai batik postmodernisme, mengangkat spirit lamadengan gaya yang baru.Kata kunci: motif, batik, postmodernisme, lukis, Yogyakarta